Impact of Safety Leadership on Safety Climate in Process Industry Workers: Literature Review - Titus Halomoan Mg; Zulkifli Djunaidi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: Safety climate concerns individual perceptions of safety policies, procedures, practices and behavior in the work environment. The low safety climate increases the risk of work accidents. Improvement safety climate, one of which can be done by increasing safety leadership, which is safety leadership bring policy direction and commitment regarding the importance of occupational safety and health. This research aims to determine the effect safety leadership to safety climate in process industry workers. Method: This research uses the "PRISMA” or preferred reporting items for systematic reviews and meta-analyses. In searching for relevant research using database google scholar and Sciendirect, with keywords “safety leadership”, “safety climate" And “process industry worker”.The total number of journals that meet the inclusion and exclusion criteria is 4 journals indexed Q1. Results: The results of this study show that there is a direct influence between safety leadership to safety climate in a positive direction. The influence is in a positive direction indicating that there is an increase safety leadership influence on safety climate which is better. There is an indirect influence between safety leadership to safety perfomance with through safety climate. Conclusion: Safety leadership influences improving the safety climate for process industry workers. These findings can be used as reference material for improving the safety climate as well as safety performance in process industry, to reducing the possibility of work accidents.